A cross sectional study; age related traumatic injuries in Karachi - Asad, Aisha; Sanawar, Parisa; Fasih, Zurrya; Qutb, Kulsoom (International Journal of Endorsing Health Science Research, 2016)
Traumatic injury is one of the major health problems in our city due to its frequency, prevalence, costs and treatment. Traumatic injuries of sudden onset and severity may require immediate resuscitation and interventions. Serious traumatic injuries have the potential to cause prolonged disability or death. The aim of this paper is to review the frequency and types of injuries in different age groups. This paper provides a quick method to receive a primary understanding of common causes of traumatic injuries. To determine incidence, pattern and implication of injuries in different age groups. A cross sectional study was performed on a sample of 150 patients, within a period of 6 months (October 2014 - March 2015). It was taken through non probability purposive sampling, in orthopaedic surgery department of Jinnah Postgraduate Medical Centre, Karachi. An informed verbal consent was taken and pilot study was conducted to assess the validity of questionnaire. A structured questionnaire was filled; data was analysed by SPSS version 16. The study conducted on 150 people, contained 103 males (68.7%) and 47 females (31.3%). Injuries were common in middle age group (40 to 60 years). Most traumas occurred on road (61.3%). Majority of people were travelling at time of injury (54.7%). Major cause of injury was found to be transport accidents (48.7%). All the victims were not provided with first aid care in transportation. Severity at emergency room of patients was mainly moderate (52.7%). Majority of young adults suffered with hip dislocation and femur fracture (10.0%) while head injury was prevalent among (6.0%) of people. Incidence of traumatic injuries and accidents is increasing day by day. The study proved that Road traffic accident is the major cause of injury in traumatic patients. Ambulances and other emergency medical services need to upgrade their facilities during transportation. Strict laws should be made to wear seat belts/ helmets during travelling. Appropriate medical care facilities (including trauma centres) need to be established at district level, sub-divisional level to provide good and quality care to trauma patients.